Scanning electron microscopic and dye penetration evaluation of hand instrumentation techniques on formation of smear layer in root canal preparation: An In vitro study - Vineet Galhotra; Ankur Chauhan; Sagar H Mohkar; Amit Heda; Govind Nandkumar Agrawal; Aniket Chavan (Wolters Kluwer Medknow Publications, 2021)
Aims and Objectives: The present study was undertaken for evaluating various hand instrumentation techniques with different instruments in the formation of smear layer. Materials and Methods: One hundred and seventy-five extracted mandibular molars were collected and were cut at cementoenamel junction. Afterward, the distal roots were separated. Working length was determined, and roots were divided into five equal groups with 35 roots in each group as follows: Group A: K-type files with conventional step-back technique, Group B: Canal Master U instrument with clockwise-counterclockwise rotation, Group C: Flex-R® files with clockwise-counterclockwise rotation, Group D: FlexoFiles® with conventional step-back technique, and Group E: Nickel titanium files with conventional step-back technique. Biomechanical preparation was done according to their respective groups. The teeth in various groups were scanned under scanning electron microscope and scoring was done. All the results were analyzed by SPSS software version 17.0. Results: Scanning electron microscopic results indicated that apparently there seems to be a significant difference in the scoring of the smear layer between each group at all the three levels, but the difference was statistically nonsignificant. Microleakage was present in all the samples. Nonsignificant results were obtained while comparing the microleakage in between different the groups. However, microleakage was highest in Group D. Conclusion: The amount of smear layer is maximum at the apical third and lesser in the middle third followed by the coronal third in all the groups. All the samples showed microleakage to a varying extent.